Decision making viva genetic algorithm for the utilization of leftovers. Issue 4 (12th January 2021) - Ali, Raiz; Muhammad, Shakoor; Takahashi, Ricardo H. C.
Abstract: Pipes have been using for different construction purposes, such as tube wells, oil wells, gas wells, and other sanitary purposes. These pipes have different sizes that can be used according to the need. In a particular construction, most of them can be used but some of them are left unused, which are known as leftovers. There are some usable leftovers (standards), whereas others are nonusable (nonstandards) leftovers. These leftovers could be difficult to manage to know which of them could be reused. The reuse of such leftovers become difficult for the construction companies to use them properly. On the other hand, these leftovers would be useful for other construction purposes rather than throw them into the bin. In this paper, we have presented a model and used a heuristic approach to make sure that the leftovers after different constructions could be reused according to the given demand. For this purpose, a genetic‐based decision support system is applied to validate the solution feasibility of the problem. Experimental results validate the effectiveness of this novel proposed model by numerical experiments, and the leftovers are minimized up to a high extent.